Menentukan Ketuaan Buah Durian Berdasarkan Sifat Ultrasoniknya - Bambang Haryanto; Hadi K. Purwadaria; I. Wayan Budiastra; A. Trisnobudi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2001)
The research was conducted to determine the maturity of durian through ultrasonic properties. For this purpose, a measurement system based on ultrasonic method was developed and controlled by a PC computer. An interface PC Lab Card was used to transfer the signal stored in the digital oscilloscope to the Personal computer. Twelve mature durians of (95 ± 3) days after fullbloom and 12 immature durians of (70 ± 3) days after fullbloom were used to determine the velocity and the attenuation. The result showed that attenuation and velocity wave of mature durians were 9.256 ± 1.077 dB/cm and 501.62 ± 44.28 m/sec, whereas the attenuation and velocity of immature ones were 6.279 ± 0.772 dB/cm and 422.36 ± 33.68 m/sec. The relationship between velocity wave of whole durians and, firmness, and velocity wave with total soluble solid were linear and significant (r2= 0.82 and r2= 0.73, respectively). Meanwhile the relationship between attenuation, and firmness, and attenuation with total soluble solid were exponential with correlation r2= 0.69 and r2= 0.67, respectively. The firmness and total soluble solid of durian flesh has strong correlation (r2= 0.92)